Specific task anticipation versus unspecific orienting reaction during early contingent negative variation - Bender, Stephan; Resch, Franz; Weisbrod, Matthias; Oelkers-Ax, Rieke (Clinical neurophysiology, 2004)
Objective: To investigate whether a warning stimulus in a forewarned reaction time task elicits only an unspecific orienting reaction or task specific motor cortex activity. Methods: We examined the time-course of alpha event-related desynchronization (ERD) as an indicator for primary motor cortex activation in an auditory contingent negative variation (CNV) paradigm with an interstimulus interval of 3 s in healthy subjects between 6 and 18 years using a 64 channel high-density sensor array. Results: We replicated a wide frontal distribution for the initial CNV component (iCNV), while only during late CNV (lCNV) a centro-parietal negativity resembling the ‘Bereitschaftspotential’ occurred. However, an early alpha-ERD over the central area contralateral to the side of the response movement followed the imperative stimulus already during the iCNV-interval. This early alpha-ERD was highly significantly lateralised and was even more prominent during iCNV than during lCNV indicating an activation of the contralateral sensorimotor cortex already during iCNV. Conclusions: We conclude that early task specific preparatory motor processes (which might reflect the retrieval of a motor program from memory) were elicited by the warning stimulus. These preparatory processes clearly exceeded an unspecific orienting reaction as early alpha-ERD was influenced by the side of the anticipated movement.